Polycaprolactone-20% Tricalcium Phosphate Scaffolds in Combination With Platelet-Rich Plasma for the Treatment of Critical-Sized Defects of the Mandible: A Pilot Study - Rai, B. (2014)
10.1016/j.joms.2006.11.026